Responsibility of Sea Transportation Services - Mutiara Latuheru, Paulina; Priambudi, Miko; Victoria, Ong Argo (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2020)
This study aims to determine the responsibility of the transporter due to seaworthiness and to determine the implementation of the responsibility relationship between the carrier and the passenger who does not pay the ticket. This research is empirical with data collection techniques carried out through interviews with parties related to the research topic. In addition, the author also conducts library research through data and books related to the research topic. Furthermore, the data obtained were analyzed qualitatively which was then presented descriptively. The results of this research are: 1) the ship provided by the carrier must meet safety requirements (seaworthy). Ship safety requirements are determined through ship classification in order to determine the designation and route of certain ships, The number of passengers must be in accordance with the capacity of the ship's cargo, and the ship's crew who have met the requirements stipulated in the law, as well as ship equipment that is in accordance with the applicable laws and standard operating procedures. 2.) Based on the internal regulations of PT. Pelayaran Indonesia (PELNI) has several actions that can be taken for passengers who do not have tickets or illegal passengers such as being dropped off at the nearest port, ordered to pay or have their luggage confiscated, being employed to the port of destination, and put in a ship's cell.